The sawflies of Namibia and western South Africa (Symphyta, Hymenoptera). - Koch, F.; Goergen, Georg E.; Noort, S. van (Belgian National Focal Point, 2015)
This monograph includes a history of the study of the sawflies of the Afrotropical Region; recommended collecting methods; a general description of the life cycle of sawflies; and extensive references to Afrotropical sawflies. A total of 55 species of Symphyta have been reported from the study area, which comprises Namibia and the western parts of South Africa. Previously, 26 species were known from Namibia and 29 species, including four introduced species, from the South African part of this region. Only one species was recorded from both countries. Identification keys for all families, genera and species are provided. As a result of current taxonomic revisions, five new junior synonyms are proposed: Athalia limpopo Benson, 1962 syn. n. for A. brevicornis Benson, 1962; A. xantha Benson, 1962 syn. n. for A. incomta Konow, 1908; A. elisabethae Muche, 1979 syn. n. for A. ustipennis Mocsáry 1909; Distega braunsi Enslin, 1911 syn. n. and D. brunniventris Enslin, 1913 syn. n. for D. montium Konow, 1907. Finally, Distega nigeriae Forsius, 1927 sp. rev. is a valid species and is removed from synonymy with D. mocsaryi Enslin, 1913. Colour images of all species are included, together with line drawings of further morphological characters, and maps displaying their known distribution.